THE ROLE OF PRINCIPAL’S VISIONARY LEADERSHIP IN IMPROVING THE QUALITY OF EDUCATION: A LITERATURE REVIEW - Supriyadhi Supriyadhi; Riswanti Rini; Hasan Hariri; Sowiyah Sowiyah (International Journal of Multidisciplinary Research and Literature, 2023)
The principal's visionary leadership style is very interesting to study. The writing of this article aims to find out how the role of the principal's visionary leadership in improving the quality of education. This research uses the literature review method by examining several related articles. From the review of several articles, it shows that the principal's visionary leadership has a significant role in achieving quality in an organization/educational institution. The role of the principal's visionary leadership style in improving the quality of education is shown by several factors and characteristics that exist in the leadership style. The final result of this study concluded that a principal who has a vision, characteristics, competence, motivation, good work standards, and value-oriented is a leader who is expected to improve the quality of education